Synthesis of carbon nanotube fibers from carbon precursors with low decomposition temperatures using a direct spinning process. (November 2017) - Lee, Sung-Hyun; Kim, Hye-Rim; Lee, Taeseon; Lee, Haemin; Lee, Jinwoo; Lee, Jaegeun; Park, Junbeom; Lee, Kun-Hong
Abstract: Carbon nanotube (CNT) fibers were synthesized from ethylene, acetylene, or methane by separately injecting ferrocene and the carbon precursors during a direct spinning process. Ethylene and acetylene have low decomposition temperatures. It was difficult to synthesize CNT fibers from these precursors using the direct spinning method. CNT fibers were continuously synthesized by delaying the contact time between the catalyst particles and the carbon precursors, which provided sufficient time for catalyst growth. Changes in catalyst size from 2 nm to 20 nm were observed as a function of the catalyst formation step setting temperature (350–440 °C) and the carbon precursor injection tube length (8–310 mm), and the relationship between the catalyst size and the CNT diameter was characterized. The CNT fibers had higher IG /ID ratios when synthesized from acetylene (69.87) or ethylene (18.52) than from methane (3.61). The choice of the carbon precursor had a much larger effect on the IG /ID ratio of the synthesized CNT fibers than the other operating variables. Graphical abstract: